2009
DOI: 10.4049/jimmunol.0803458
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and Its Role in MHC-Mediated Antigen Presentation

Abstract: Intracellular degradation by autophagy plays a role in the maintenance of cellular homeostasis under normal conditions and during periods of cellular stress. Autophagy has also been implicated in several other cellular processes including immune recognition and responsiveness. More specifically, autophagy has been identified as a route by which cytoplasmic and nuclear Ag are delivered to MHC class II molecules for presentation to CD4+ T cells. Autophagy has also recently been implicated in MHC class I cross-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
189
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(193 citation statements)
references
References 76 publications
0
189
1
3
Order By: Relevance
“…We have not addressed directly whether Hsp70's role in this model lies mainly in antigen-chaperoning (33,38,39) or enhancing autophagy (40) or triggering DC maturation (41,42) with subsequent increase in T-cell stimulation. All of these known functions can be important and they likely play a synergistic role.…”
Section: Discussionmentioning
confidence: 99%
“…We have not addressed directly whether Hsp70's role in this model lies mainly in antigen-chaperoning (33,38,39) or enhancing autophagy (40) or triggering DC maturation (41,42) with subsequent increase in T-cell stimulation. All of these known functions can be important and they likely play a synergistic role.…”
Section: Discussionmentioning
confidence: 99%
“…The vacuolar/endolysosomal pathway was proposed as a significant, nonproteasomal degradation pathway for a variety of cytosolic and membranal proteins (64). The endolysosomal pathway was studied more for its involvement in producing the HLA class II peptidomes (reviewed in (16,17)) and for cross presentation of HLA class I peptides ((65), reviewed in (22, 66 -68)). Furthermore, although the proteasome was proposed as the main protease responsible for degradation of newly synthesized proteins, including DRiPs and SLiPs, autophagy and lysosomal proteolysis were mostly associated with degradation of long-lived, house-keeping proteins and whole organelles at the end of their functional lifecycles (64).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the mostly cytoplasmic and ER production of the MHC class I peptidome, the class II peptidome is produced in a special compartment, associated with the endolysosome pathway (18 -20). This pathway is also thought to participate in the cross presentation of class I peptides, derived from proteins up-taken by professional antigen presenting cells (21), (reviewed in (15)(16)(17)22)). …”
mentioning
confidence: 99%
“…The autophagy is a mechanism for elimination of old or damaged organelles and insoluble proteins aggregates (61). In addition, autophagy has important immune functions because it is implicated in elimination of intracellular pathogens, the delivery of TLR ligands in endosomal compartments (62), and antigen presentation (63). TLR signaling is involved in the autophagy regulation both through MyD88-dependent and -independent mechanism(s) (64 -67), and it has been found that activation of macrophages and dendritic cells with TLR ligands results in formation of ALIS in which polyubiquitinated aggregates are directed by p62 to autophagosomes (32).…”
Section: Discussionmentioning
confidence: 99%